Control of psycho-physiological functions of students with ophthalmologic diseases in the process of physical education - V.M. Koryahin; O.Z. Blavt; V.V. Stadnyk (H.S. Skovoroda Kharkov National Pedagogical University, 2017)
Purpose: to analyze dynamic of special health group students' (having ophthalmologic diseases) psychological functions parameters in physical education process. Material: in experiment 40 special health groups' students with ophthalmologic diseases participated. Psycho-physiological tests and tool methodic were used. Results: numerical values of atenciony abilities at the beginning of the research witnessed about disharmony of information's processing, transformation and storing by students. We observed general tendency to increase of test results, which in most of experimental group students (63.4%) reached average level. Improvement of motor apparatus lability witnesses about adjustment of trophic and energetic processes as well as their vegetative regulation. Integrative indicator of attention stability was at average level (5 points) at the beginning of the research. During experiment this indicator increased 2.7 times (10-11 points). We determined the presence of correlation between quickness of task's fulfillment and efficiency coefficient (r=0.655). Conclusions: the received information is a foundation for effective interaction of physical education subjects in the form of personality-oriented technology.